(untitled) (Scientia Agricola, 2013)
Appropriate management of agricultural crop residues could result in increases on soil organic carbon (SOC) and help to mitigate gas effect. To distinguish the contributions of SOC and sugarcane (Saccharum spp.) residues to the short-term CO2-C loss, we studied the influence of several tillage systems: heavy offset disk harrow (HO), chisel plow (CP), rotary tiller (RT), and sugarcane mill tiller (SM) in 2008, and CP, RT, SM, moldboard (MP), and subsoiler (SUB) in 2009, with and without sugarcane residues relative to no-till (NT) in the sugarcane producing region of Brazil. Soil CO2-C emissions were measured daily for two weeks after tillage using portable soil respiration systems. Daily CO2-C emissions declined after tillage regardless of tillage system. In 2008, total CO2-C from SOC and/or residue decomposition was greater for RT and lowest for CP. In 2009, emission was greatest for MP and CP with residues, and smallest for NT. SOC and residue contributed 47 % and 41 %, respectively, to total CO2-C emissions. Regarding the estimated emissions from sugarcane residue and SOC decomposition within the measurement period, CO2-C factor was similar to sugarcane residue and soil organic carbon decomposition, depending on the tillage system applied. Our approach may define new emission factors that are associated to tillage operations on bare or sugarcane-residue-covered soils to estimate the total carbon loss.